Peningkatan Karakter Kemandirian Siswa dalam Pembelajaran PAI Melalui Proyek Penguatan Profil Pelajar Pancasila di SMKN 1 Jombang - Halimatus Sholihah; Jumari Jumari (JURNAL ILMIAH NUSANTARA, 2024)
As an educational institution, the school's responsibility lies not only in student achievement in the fields of science and technology, but also in developing aspects of personality, character and morals. Therefore, understanding character education is very important in preparing individuals who have excellence, confidence, integrity, a strong personality, and are independent. Based on this problem, this research has three objectives. The objectives of this research are as follows: 1) To explain the character of student independence in PAI learning at SMKN 1 Jombang. 2) To explain the Project for Strengthening the Profile of Pancasila Students at SMKN 1 Jombang. 3). To explain the increase in students' independent character in PAI learning by implementing the Pancasila Student Profile Strengthening Project at SMKN 1 Jombang. This research uses a qualitative approach and descriptive methods. To obtain in-depth and comprehensive data, data collection techniques used include observation, interviews and documentation. A case study was chosen as the design of this research. The results of the research show that: 1) The independent character of students in PAI learning at SMKN 1 Jombang is improved by instilling the values ​​of Islamic teachings in the students as well as instilling the character of independence through the learning process in the form of presentations, so that it becomes one of the exercises to improve the character of independence. 2) The Project for Strengthening the Profile of Pancasila Students at SMKN 1 Jombang takes the form of co-curricular learning, taking 3 themes. 1 mandatory theme, namely the theme of work and 2 optional themes, namely the theme of the voice of democracy and the theme of Bhinneka Tunggal Ika. 3) increasing students' independent character in PAI learning is carried out with assignments in the form of presentations. Through the implementation of the project to strengthen the profile of Pancasila students at SMKN 1 Jombang during PAI learning, students showed a higher level of self-confidence and more skilled independence.